PENGGUNAAN MEDIA POWERPOINT INTERAKTIF UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS III SD NEGERI CORONGAN - Miska Risky, Novianna; Nadziroh; Alfiyah, Alfiyah (Universitas Sarjanawiyata Tamansiswa, 2022)
Educational reforms can be carried out on the use of learning media. PowerPoint can be used as a learning media. The features in PowerPoint are variations in the delivery of material so that it can foster student learning motivation. The purpose of this study was to determine the increase in thematic learning motivation of third-grade students of SD Negeri Corongan using PowerPoint as a learning media. This type of research is Classroom Action Research (CAR). The subjects in this study were students of class III SD Negeri Corongan. Data collection techniques using questionnaires, observation, and documentation techniques. The results showed that the use of PowerPoint media can increase students' learning motivation. The pre-action observation had an average score of 52%. Based on the results of observations in the second cycle with a percentage of 83%. The increase in student motivation is also shown in the results of the questionnaire analysis. The results of the questionnaire in the second cycle with a percentage of 82%. Based on the results of this study, it is expected that teachers will consider the use of PowerPoint media to increase students' learning motivation in elementary schools.